Forecasting teacher demand - Petkus, Tomas; Kurasova, Olga; Ciunel, Ilona (Information & Media, 2016)
In this paper, the demand of teachers has been forecasted up to the year 2024. The criteria affecting the forecast of the teacher demand have been chosen. It has been indicated how the number of pupils are forecasted taking into consideration the birth rate and the number of pre-school children, the change of pupils moving from a lower to a higher class. The distribution of teacher age affecting the forecast of the teacher numbers has been also investigated. The number of new prepared teachers has been evaluated. The demand of teachers (excess or deficiency) has been calculated taking into account the forecasted number of pupils, the age of teachers, the number of students, graduated teacher training programs. The forecast shows when the deficiency of teachers of physics, mathematics, the Russian language, chemistry, information technology and other subjects will appear.
Keywords: ...